Post EraMethod in Teaching Indonesian Language and Literature in Elementary School - Dian Indihadi; Risnandar Sudarman (Indonesian Journal of Primary Education, 2021)
This study aims to explain the Post Method era in teaching language and literature in elementary school. This study uses a qualitative approach with library study methods or Library Research. Library studies as a data collection technique by conducting study studies on books, literature-literature, records, and reports that have to do with problems solved. This study utilizes journals, materials and relevant information to be collected, read and studied, recorded as guidelines or reference sources. The literature study method in this study can be used as data and data sources regarding the topic of problems. In the post-method era, language teaching is done not only based on certain methods. Language teaching can adopt several different methods and techniques at the same time. So, we can say that even though there are still methods in the post-method era, but we don't depend on certain methods. The first post-method era is not an era where no method is used in Indonesian language and literary teaching. Second, the method used in language teaching can be a combination of several methods in accordance with the teaching needs of Indonesian language and literature.